Song in a rainstorm : the story of musical prodigy Thomas "Blind Tom" Wiggins - Armand, Glenda (Albert Whitman & Company, 2021)
Born blind into a life of slavery in Georgia, Thomas Wiggins was dismissed as a "useless burden." But through the loving protection of his family, he went on to become one of the greatest musicians of his time --